Martelaren van Chicago, gerechtelijk vermoord op 11 november 1887. Uit: archief F. Domela Nieuwenhuis, VI a 1 (B), no. 15
Martelaren van Chicago, gerechtelijk vermoord op 11 november 1887. Uit: archief F. Domela Nieuwenhuis, VI a 1 (B), no. 15.